For youth workers and youth work : speaking out for a better future - Nicholls, Doug (Policy Press, 2012)
In this unique and passionate book, Doug Nicholls proposes a cultural revolution within youth work. He draws on the best of youth work's past to redesign the youth work map for today. He speaks with wit, wisdom and warmth to youth workers about their craft. Yet he takes no intellectual prisoners in proposing a new role for youth work in the struggle for social justice. No student or practitioner should miss it.